The Relationship between Personality Traits and Health Information-Seeking Behavior of Users of Public Libraries Based on Miller\'s Theory - Maryam Ghanbari Khoshnood; Zeinab Safavi; Parvin Derikvand; Fateme Rastegary (تحقیقات اطلاع‌رسانی و کتابخانه‌های عمومی)
Purpose: Personality traits are effective in information seeking behavior. The present research was conducted with the aim of discovering the relationship between personality traits and health information seeking behavior of users of the central library of Hamadan province based on Miller's theory. Method: The type of this study is applied and its method is a survey. The research population included all 4638 users of the central library of Hamadan province. According to Morgan's table, the sample size was 355 people and 346 questionnaires were used in the final analysis. The tools of data collection were the standard questionnaires of Five Neo Personality Factors and Miller's Health Information Seeking Behavior. Data analysis was done at two levels of descriptive and inferential statistics using SPSS 26. Findings: 75.4% (261 people) of the studied population actively search for health information and 24.6% (85 people) consciously avoid searching for health information. There is a high and significant relationship between the personality traits of Extroversion, Agreeableness and Passion for New Experiences with the component of active search for health information and there was a low and significant relationship between the three mentioned personality traits with the conscious avoidance of health information search component. There was no significant relationship between the personality traits of Emotional Stability and Conscientiousness with the components of health information seeking behavior. The results of multiple linear regression analysis to predict the conscious search for health information through personality traits showed that the personality traits Extroversion, Agreeableness and Openness with predicting 42.9 percentage of the variance of the dependent variable is a good indicator for explanation. In predicting conscious avoidance of seeking health information through personality traits, it was found that the personality traits Extroversion, Agreeableness and Passion for new experiences explained 36.3% of the variance of the dependent variable. It can be said that they are a good indicator for explanation. Originality/value: The findings of this research based on the importance of public health knowledge and the influence of personality traits on the way of seeking health information and the type of preventive behaviors to deal with stressful events can help managers and planners of public libraries in making decisions related to the provision of resources according to the personality characteristics and training users for health information seeking skills. The results of the present research, by determining the prevalence of personality traits of Extroversion, Agreeableness and Openness of the studied users shows the necessity of librarians' efforts in providing services by considering these characteristics and promoting services and information resources according to users’ other personality traits and behavioral characteristics.